Complexation Enhanced Excited‐State Deactivation by Lithium Ion Coordination to a Borondipyrromethene (Bodipy) Donor–Bridge–Acceptor Dyad. Issue 30 (4th September 2013) - Benniston, Andrew C.; Yang, Songjie; Lemmetyinen, Helge; Tkachenko, Nikolai V.
Abstract: A donor–acceptor dyad was prepared comprised of a borondipyrromethene (Bodipy) chromophore as the acceptor and a dimethylamino moiety as the donor. The two groups are separated by a 2, 2′‐biphenol moiety. The excited state of the Bodipy is efficiently quenched by electron transfer involving donation from the dimethyl amino group. The rate constant for forward electron transfer in DMF was measured to be ca. 2 × 10 10 s –1 . The charge recombination process is ultrafast. Titration of aliquots of LiClO4 to a DMF solution of the dyad resulted in alterations to the absorption spectrum associated with the 2, 2′‐biphenol unit. Changes were modelled as Li + ions bound to the oxygen atoms of the 2, 2′‐biphenol to produce 1:1 (Li + /ligand) and 2:1 (Li + /ligand) complexes. The rate constant for excited state quenching is enhanced upon lithium ion binding. Abstract : A Bodipy‐based dyad comprising a donor–bridge–acceptor motif was prepared. Fast electron transfer occurs from the amino donor to the Bodipy acceptor following excitation. The complexation of lithium ions to the 2, 2′‐biphenol group in the bridge facilitates through‐bridge electron transfer.